Periphytic algae of two bioforms of macrophytes in a subtropical shallow lake of Argentina - Vallejos, Silvina Vanesa (2015)
The aim of this study was to analyse the structure and temporal variations in density and diversity of periphytic algae from Potamogeton illinoensis Morong (submerged and perennial macrophyte) and Nymphoides indica (Linné) Kuntze (rooted fl oating leaves and seasonal growth). The study was conducted in a shallow lake in northeastern Argentina (27° 29’ S; 58° 45’ W), between March 2007 and February 2010. Sixty-one taxa were exclusive to P. illinoensis, 12 were exclusive to N. indica, and 54 were common to both. Density, number of species and diversity were comparatively higher in P. illinoensis than in N. indica. Cyanobacteria (mainly Stigonema hormoides Bornet & Flahault) were dominant in P. illinoensis, whereas Chlorophyta (Oedogonium spp.) were dominant in N. indica. Potamogeton illinoensis developed a stable, mature epiphytic community over time. In N. indica, the density and diversity of periphytic algae were related to the plant seasonality and water level fl uctuations.